Metasurface-driven polarization-division multiplexing of PCSEL for optical communications - Wen-Chien Miao; Chia-Hsun Chang; Fu-He Hsiao; Yun-Han Chang; Jhih-Hao Huang; Huan-Teng Su; Chang-Yi Lin; Chun-Liang Lin; Chi-Wai Chow; Yu-Heng Hong; Yao-Wei Huang; Hao-Chung Kuo (Discover Nano, 2023)
Abstract Free-space optical communications hold promising advantages, including a large bandwidth, access to license-free spectrum, high data rates, quick and simple deployment, low power consumption, and relaxed quality requirements. Nevertheless, key technical challenges remain, such as a higher transmission efficiency, a lower transmission loss, and a smaller form factor of optical systems. Here, we demonstrate the viability of circular-polarization-multiplexed multi-channel optical communication using metasurfaces alongside a photonic-crystal surface-emitting laser (PCSEL) light source at wavelength of 940 nm. Through the light manipulation with metasurface, we split the linearly polarized incidence into left and right circular polarizations with desired diffraction angles. Such orthogonal polarization states provide a paradigm of polarization division multiplexing technique for light communication. The PCSEL light source maintains a low divergence angle of about 0.373 degrees after passing through an ultra-thin metasurface without further bulky collimator or light guide, making end-to-end (E2E) and device-to-device (D2D) communications available in a compact form. Both light source and modulated polarized light exhibit a − 3 dB bandwidth over 500 MHz, with successful 1 Gbit/s transmission demonstrated in eye diagrams. Our results affirm that metasurface effectively boosts transmission capacity without compromising the light source's inherent properties. Future metasurface designs could expand channel capacity, and its integration with PCSEL monolithically holds promise for reducing interface losses, thereby enhancing efficiency.